Pembelajaran dengan Metode Kisah (storytelling): Ekstensi dan Intensi Metode Linguistik dalam Bahasa Al Qur’an dengan Bentuk Imperatif - Siswati, Via Linda (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Long before writing, the only culture was oral and oral culture. Storytelling means participating, and helping children participate, in one of the most ancient human habits. The meaning we can draw from Gabriel's hadith as a way to understand the world of 'religious meaning' and be reminded that formal learning remains significant but that, interestingly, the Qur'an does not mention these activities while imperatively declaring "telling stories story (fa-qsis al-qasas) ". This paper aims to describe: how learning with storytelling methods: extension and intention of linguistic methods in the language of the Qur'an with an imperative form. The results of the discussion can be summarized as follows: the imperative statement in the verses of the Qur'an is not strange; has been the subject of much debate. The commandment has been mentioned in various forms in the Quran which imply reproach, ridicule, obedience, exclamation and so on. This method is associated with the rhetorical aspects of the Quran while the rhetoric is related to the linguistic wonders of the Quran